An embedded fuzzy controller for a behavior-based mobile robot with guaranteed performance. - Yang, S.X (IEEE Transactions on fuzzy systems)
In this paper, an embedded fuzzy controller for a nonholonomic mobile robot is developed. The mobile robot was built based on the behavior-based artificial intelligence, where several levels of competences and behaviors are implemented. A class of fuzzy control laws is formulated using the Lyapunov's direct method, which can guarantee the convergence of the steering errors. Theoretical analysis of the fuzzy control algorithms for steering control of the mobile robot is performed. The requirements for a suitable rule base selection in the proposed fuzzy controller are provided, which can guarantee the asymptotical stability of the system. Simulation and experimental studies are conducted to investigate the performance of the proposed fuzzy controller. It can achieve the desired turn angle and make the mobile robot follow the target trajectory satisfactorily.